Integration Concepts of the Lands Inhabited by Albanians - Katarzyna Kropiak (Ksiegarnia Akademicka Publishing, 2014)
The provisions of the London Conference of 1913 established a new balance of powers after the first Balkan war. It was to guarantee the respect of interests and provide the territorial integrity of the newly created national countries, however, in reality it was the reflection of the political interests of the powers. The Ottoman occupation of the Balkans led to the situationin which different ethnic communities inhabited the same territories together. The principality of Albania was established in the borders, which only partially overlapped with the area inhabited by Albanians. Beyond the borders of Albania established in 1913 there were, among others, Kosovo and northern‑western Macedonia, inhabited by Albanians at the end of the XVI century until the beginning of the XIX century as a result of the economic migrations and numerous resettlements of the people. The decisions of the London Conference on the borders of Albania were to guarantee the ethnic homogeneity of the state’s territory. On the example of the history of the Autonomous Republic of the Northern Epirus it can be argued that this assumption has not been completely satisfied. Although outside the borders of the Albanian state there were many areas where the Albanians were the majority, the borders of the principality were determined in a way which was to guarantee the territorial integrity of the newly created country. Within the borders of Albania there were various clans previously included in various Vilayets, which professed different religions. In case of other ethnic groups, the religious factor had a highly destabilising significance. It is worth mentioning that in the initial period of the existence of the country, there was no centre of the strong political leadership (Wilhelm zu Wied emigrated after several months). The factor which consolidated the population living in the newly created country was the Albanian language, different from the languages of the region and the activity of the National Revival Movement, which placed a strong emphasis of the mythologisation of the Albanian history. The listed conditionings has strong impact on the population experiencing the membership to the Albanian nation also beyond the borders established in London and Florence. The demarcation of the borders of the state not coinciding with the ethnic borders made the border area at the turn of the XX and XXI century become the area of conflict.